Antidepressant treatment with venlafaxine and mirtazapine: no effect on serum concentration of Vascular Endothelial Growth Factor (VEGF) - Deuschle, Michael (Pharmacopsychiatry, 2015)
Introduction: Depression, stress and antidepressant treatment have been found to modulate the expression of growth factors. Methods: We studied depressed patients receiving randomized treatment with venlafaxine or mirtazapine for 28 days. Results: There was no significant difference between baseline VEGF concentrations in depressed patients compared to healthy controls. We found no significant effect of antidepressant treatment on serum VEGF. Discussion: In contrast to serum BDNF, VEGF may not be a suitable biomarker for effects of antidepressant treatment with venlafaxine or mirtazapine.